Avaliação da bioacessibilidade de compostos fenólicos de polpas de frutas nativas e exóticas oriundas dos distintos biomas brasileiros - Dantas, Aline Macedo (2018)
In the different biomes of Brazil are produced a great diversity of native and exotic fruits. The largest production is concentrated in the Amazon Forest, Cerrado, Atlantic Forest and Caatinga biomes. Currently, some of these fruits, such as açaí, cupuaçu, graviola, raspberry, jabuticaba, blackberry, blueberry and cajá, present a high demand in the internal and external markets, due to the beneficial effects on the health of the consumer, particularly due to the nutritional composition and presence of bioactive compounds responsible for high antioxidant activity. Studies on the profile of phenolic compounds and antioxidant activity in fruit pulps are still scarce, however, they are important to elucidate their functional potentialities, and thus, contribute to the expansion of their consumption, due to the growing search for products that provide health benefits. This work aimed to evaluate the bioaccessibility of phenolic compounds and antioxidant activity of Brazilian fruit pulp after gastrointestinal digestion in vitro. The fruit pulps used in this experiment were obtained from several Brazilian agroindustries, all complying with the standards of identity and quality required by the legislation in force in Brazil. In vitro gastrointestinal digestion simulated the conditions of enzymatic hydrolysis of the mouth (a-amylase), stomach (pepsin) and intestine (pancreatin) coupled with a dialysis membrane for simulation of the intestinal wall. The bioaccessibility of phenolic compounds was determined from the percentage of the dialysate fraction. For the identification and quantification of phenolic compounds the liquid chromatography system was coupled to the UV detector. The antioxidant activity of the dialysate fraction was evaluated by DPPH• capture methods. and the reducing capacity of Fe +2. Principal components analysis was applied to verify similarities and differences between the groups of phenolic compounds and methods of evaluation of antioxidant activity. The content of phenolic compounds and their bioaccessibility varied in the fruit pulp studied. The highest content of phenolic compounds was found in the blueberry pulp followed by graviola, açaí, raspberry, blackberry, cajá, cupuaçu and jabuticaba. The results demonstrated a greater bioaccessibility of flavonoids and phenolic acids in relation to anthocyanins. The highest bioaccessibility was found in catechin, procyanidins, quercetin 3-glucoside, rutin, syringic acid, caftaric acid, chlorogenic acid and cis resvesratrol, contributing to antioxidant activity. Changes in the content of phenolic compounds reflected in the reduction of antioxidant activity after simulation of gastrointestinal digestion in vitro. The results showed that in vitro gastrointestinal digestion influences the content of phenolic compounds and the antioxidant activity of fruit pulp. In addition, blackberry and cajá fruit pulps demonstrated the highest values of bioaccessibility and antioxidant activity, and their consumption through diet may contribute to the increase of endogenous antioxidant activity.